2011
DOI: 10.1890/10-2047.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative recommendations for amphibian terrestrial habitat conservation derived from habitat selection behavior

Abstract: Conservation scientists have noted that conservation managers rarely use scientific information when making decisions. One of the reasons why managers rarely use scientific information may be that conservation scientists rarely provide their knowledge in a way that can directly be used by conservation practitioners. Here we show how quantitative recommendations for conservation can be derived. Previous research on terrestrial habitat selection behavior of toads (Bufo bufo and Bufo viridis) showed that wood dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We found that sites that were colonised were associated with higher levels of coarse woody debris (Table 1) which is likely to provide an important refuge for new colonisers (Hazell et al, 2003). Coarse woody debris is a key resource for some amphibians (Indermaur and Schmidt, 2011) and its addition could potentially be used to encourage L. v. verreauxii colonisation. Sites that supported frogs in both survey periods were associated with lower levels of bare bank and higher levels of tussock in the riparian zone (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We found that sites that were colonised were associated with higher levels of coarse woody debris (Table 1) which is likely to provide an important refuge for new colonisers (Hazell et al, 2003). Coarse woody debris is a key resource for some amphibians (Indermaur and Schmidt, 2011) and its addition could potentially be used to encourage L. v. verreauxii colonisation. Sites that supported frogs in both survey periods were associated with lower levels of bare bank and higher levels of tussock in the riparian zone (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, newt survival has been shown to be higher on land than in the water in another newt species (Unglaub, Steinfartz, Drechsler & Schmidt, 2015). Previous studies showed the importance of the forest in the core zone around the breeding ponds of amphibians including newts (Denoël & Ficetola, 2008;Gustafson, Malmgren & Mikusiński, 2011;Indermaur & Schmidt, 2011). Indeed, forests can contain moist and shaded ground, which is favourable for feeding, but also for migration, aestivating and overwintering (Jehle & Arntzen, 2000;Marty, Angélibert, Giani & Joly, 2005;Schabetsberger, Jehle, Maletzky, Pesta & Sztatecsny, 2004).…”
Section: Impact Of Fish Presence On Habitat Use In Newtsmentioning
confidence: 99%
“…We do not know the cause for the variation in density among the three areas. It may be related to social interactions, resource availability or habitat quality [33][34][35]. Further studies that link density to resource selection and or variation in habitat quality may therefore be worthwhile [36].…”
Section: Discussionmentioning
confidence: 99%